استثمار الوقف العقاري من خلال الكراوفندينج في القانون الجزائري - براحلية, بدرالدين (جامعة الوادي University of Eloued, 2019)
يعتبر الكراوفندينج أداة حديثة تستخدم في عديد المجالات لتفعيل دور المواطنين في تسيير المرافق العامة. يناقش المقال استثمار الوقف العقاري من خلال الكراوفندينج في القانون الجزائري، ويلخّص التنظيم القانوني للكراوفندينج في الأنظمة القانونية المقارنة مع التركيز على تجربة الشركات الماليزية. يكشف البحث عن آليات عمل منصات الكراوفندينج، ويوصي بتبنّيها في القانون الجزائري كنوع من عقود تفويض المرفق العام. The Crowdfunding has been utilized in multi-sectors as a new method to revitalize the role of the citizens in the management of the public utilities. The paper discusses the investment of Waqf Land through the Crowdfunding in Algerian Law. It summarizes the regulation of the Crowdfunding in the comparative legal systems, and focusing on the experience of the Malaysian firms. The research explores the working mechanisms of the Crowdfunding platforms and recommends their adoption in the Algerian law as a type of a public service delegation contract.
The Investment Of Waqf Land Through The Crowdfunding In Algerian Law
Keywords: الكراوفندينج؛ تفويض المرفق العام؛ استثمار؛ الوقف العقاري; Crowdfunding; Public Service Delegation; Investment; Waqf Land